Basics of the structure of the financial investment management process: risk analysis and control, their influence on decision-making - Vasilieva, Lesya; Васільєва, Леся Миколаївна (Дніпровський державний аграрно-економічний університет, 2024)
During the examination of the financial investment management process, the main division of participants into those who invest capital and those who seek to receive this capital was revealed. Among the main features of the process of managing financial investments, the need to build an investment policy of a business entity was identified, which would fix the main aspects of the entity's strategy both from the side of the investor and the object of investment, this in turn demonstrates to us an additional feature, which was established in the research process: each business entity performs several roles in the course of functioning, which have their own characteristics. With the aim of forming a strategy and, accordingly, building an investment policy of a business entity, which would highlight the main decisions of investment activity, the risks that have a direct impact on the business entity were considered, their main forms of manifestation, causes of occurrence and methods of implementation were identified. A characteristic feature of risks in investing was the absence of "pure" risks: they always appear in two or more forms; simultaneously with the impact on the investment, the same risk can have an impact on the investor, which determines the need to build a system of countermeasures and prevention of risks while simultaneously accepting them for obtaining additional income. Taking into account the risks that accompany the investment process and the investor's ability to accept them, through the assessment of the investor's risk profile, 94 the main strategies for managing financial investments are established, the methods of their implementation and their features are determined. Having considered the basics of the process of managing financial investments, we come to the conclusion that these basics can be used not only to determine the investment strategy of a business entity, but also to build control tools in order to counteract the dangers encountered Під час розгляду процесу управління фінансовими інвестиціями було виявлено основний поділ учасників на тих, хто вкладає капітал та тих, хто цей капітал прагне отримати. Серед основних особливостей процесу управління фінансовими інвестиціями було виявлено необхідність побудови інвестиційної політики суб’єкта господарювання, яка б закріплювала основні аспекти стратегії суб’єкта як з боку інвестора, так і об’єкта вкладення, це у свою чергу демонструє нам додаткову особливість, яка була встановлена в процесі дослідження: кожен суб’єкт господарювання в ході функціонування виконує декілька ролей, які мають свої особливості. З метою формування стратегії та, відповідно, побудови інвестиційної політики суб’єкта господарювання, яка б висвітлювала основні рішення інвестиційної діяльності розглянуто ризики, які здійснюють безпосередній вплив на суб’єкт господарювання, виявлено їх основні форми прояву, причини виникнення та способи реалізації. Характерною особливістю ризиків в інвестуванні було визначено відсутність «чистих» ризиків: вони завжди проявляються у двох та більше формах; одночасно з впливом на інвестицію, один й той самий ризик, може чинити вплив й на інвестора, що й визначає необхідність побудови системи протидії та попередження ризиків з одночасним їх прийняттям за для отримання додаткового доходу. Враховуючи ризики, які супроводжують процес інвестування та здатність інвестора до їх прийняття, – через оцінку ризик-профілю інвестора, – встановлено основні стратегії управління фінансовими інвестиціями, визначено способи їх реалізації та особливості. Розглянувши основи процесу управління фінансовими інвестиціями доходимо висновку, що ці основи можуть використовуватися не лише для визначення інвестиційної стратегії суб’єкта господарювання, а й для побудови засобів контролю з метою протидії небезпекам, що спіткають.
Основи побудови процесу управління фінансовими інвестиціями: аналіз та контроль ризику, їх вплив при прийнятті рішень
Keywords: analysis; аналіз; information; інформація; risks; ризики; management; управління; financial investments; фінансові інвестиції